2019
DOI: 10.1080/13621718.2019.1630571
|View full text |Cite
|
Sign up to set email alerts
|

Achieving equal fatigue strength to base material in a friction stir welded 5083-H19 aluminium alloy joint

Abstract: By using a low rotation rate of 200 rpm with additional water cooling, a friction stir welded (FSW) joint with equal fatigue strength to the base material (BM) was obtained in 5083Al-H19 rolled plates due to the significantly decreased softening and the residual stress effect. Though the hardness value in the heat affected zone (HAZ) was a little lower than that of the BM, the decreased tensile effect of the residual stress in the HAZ greatly improved the fatigue performance, which was even higher than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…Apart from this, the hardness in NZ is more significant than which is obtained in HAZ and TMAZ, and smaller hardness value was obtained at the boundary between the HAZ and TMAZ. 22 As the TRS, WS increased, higher hardness is obtained with a narrower TZ. It is suggested that aluminum alloy produces w-shaped hardness profile.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…Apart from this, the hardness in NZ is more significant than which is obtained in HAZ and TMAZ, and smaller hardness value was obtained at the boundary between the HAZ and TMAZ. 22 As the TRS, WS increased, higher hardness is obtained with a narrower TZ. It is suggested that aluminum alloy produces w-shaped hardness profile.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…The fine precipitates of Mg 2 Si and the subsequent formation of smaller grains in the aluminium matrix are the reason for this high fatigue strength. Similarly, Wang et al [44] have done a research to achieve equal fatigue strength to base material in a friction stir welded 5083-H19 aluminium alloy joint. Authors achieved base material fatigue strength of about 200 MPa in the FSW plate after the careful fixing of the process parameters.…”
Section: Fatigue Behaviourmentioning
confidence: 99%
“…The BM has a relatively high fatigue strength of 140 MPa; however, the fatigue strength of both the 300-200 and 300-400 joints decreased to 110 MPa (78% of BM). The relationship between the maximum stress and number of cycles to failure under the condition of HCF can be fitted by the following Basquin equation [2,[46][47][48][49]:…”
Section: High-cycle Fatigue Propertiesmentioning
confidence: 99%